Linear IgA bullous dermatosis secondary to drugs: a real-world pharmacovigilance study of the FDA adverse event reporting system - Yang, Yixuan; Xie, Hanzhang; Liu, Shuhan; Jia, Ying; Cui, Bingnan; Xiao, Zhanshuo (Frontiers in Medicine, 2025)
BackgroundLinear IgA bullous dermatosis (LABD) is a rare autoimmune blistering disease. The induction of LABD by medications is a critical issue, with previous studies highlighting the link between specific drugs and the onset of LABD. This study aims to assess the reported associations between LABD and numerous available medications using the FDA adverse event reporting system (FAERS).MethodsThe study encompassed FAERS reports spanning the years 2004–2024. Medical Dictionary for Regulatory Activities (MedDRA) was used to identify cases of LABD. The Reporting Odds Ratio, Proportional Reporting Ratio, Bayesian Confidence Propagation Neural Network, and Empirical Bayes Geometric Mean were calculated to assess the reported associations between available drugs and LABD. A significant statistical association was considered when a drug signal met the criteria of all four algorithms.ResultsIn the FAERS database analysis, we identified 1,394 adverse event (AE) reports associated with LABD. The gender distribution of reports was relatively balanced, with the highest proportion in the 66–85 age group. The United States had the highest number of reports. Vancomycin and Amoxicillin were the most frequently reported drugs, with 559 and 58 reports, respectively. Through disproportionality analysis, we identified 34 drugs significantly associated with AEs of LABD, including antibiotics, antifungal medications, analgesics, nonsteroidal anti-inflammatory drugs, cardiovascular medications, and calcium channel blockers, among which the antibiotic Vancomycin showed the highest association. These results emphasize the need for further clinical attention to the safety of specific medications.ConclusionThis is the first real-world study using the FAERS database to investigate drug-induced LABD. LABD is closely associated with antibiotic medications. Close monitoring of patients is required when these medications are used clinically to promptly detect and manage potential AEs such as LABD.